Emotional quotient in children and adolescents from Boyacá, Colombia: a comparative study - Buitrago, Rafael Enrique; Herrera, Lucía; Cárdenas, Ruth Nayibe (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article makes a comparative analysis of emotional intelligence of Colombian children and young students aged from 8 to 10 year-old and from 11 to 16 years-old. The study sample was 1451 students from three provinces in the Department of Boyacá. The research was carried out from a quantitative perspective. Emotional Quotient Inventory: Youth Version [EQ-i: YV] was used for data collection. Both the reliability and the validity of the EQ-i: YV were determined for the sample. The main results showed some differences in emotional intelligence according to age range. Children achieved better results than adolescents in stress management and adaptability scales.